ACERCA DE LA PRETENDIDA SUBSTANCIA ANTAGONISTA DE LA VASOPRESINA DEL SUERO DE EMBARAZADA NORMAL - VERGARA SOTO, E; GUTIERREZ NAVA, ROGELIO (Laboratorio de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1942)
Nucleoli were counted in lymphocytes of 6 lepers, and Rn (riqueza nucleolar) index detd This was found to be higher (096) than that in normal blood No lymphocytes were found with more than 3 nucleoli A correlation was seen between change in Rn index a
BOL INST ESTUD MED BIOL
Keywords: SUBSTANCIA, ANTAGONISTA, VASOPRESINA, SUERO, EMBARAZADA; CIENCIAS MEDICAS; CIENCIAS CLINICAS; GINECOLOGIA